EFEKTIVITAS EFEKTIVITAS GERAKAN LITERASI DALAM MENINGKATKAN MINAT BACA SISWA KELAS VII MTs TARBIYATUL AULAD TEBANAH: EFEKTIVITAS GERAKAN LITERASI DALAM MENINGKATKAN MINAT BACA SISWA KELAS VII MTs TARBIYATUL AULAD TEBANAH - Abdul Azis; Moh. Ari Wibowo; Jatim Desiyanto (Jurnal Cendekia Pendidikan, 2024)
Reading expands knowledge. The more reading activities, the deeper the knowledge you gain. Reading is an activity to extract meaning from text whose aim is to develop knowledge and potential. The aims of this research are: 1) To determine teachers' efforts to overcome or foster interest in reading through the literacy movement at Madrasah Tsanawiyah Tarbiyatul Aulad Tebanah Banyuates Sampang; 2) To determine the effectiveness of the literacy movement at Madrasah Tsanawiyah Tarbiyatul Aulad Tebanah Banyuates Sampang; 3) To find out the advantages and disadvantages of the literacy movement at Madrasah Tsanawiyah Tarbiyatul Aulad Tebanah Banyuates Sampang. This research uses qualitative research with a descriptive analysis approach because this research is aimed at obtaining the factors that occur in the history of the history of the problem. Effectiveness of the Literacy Movement to Increase the Quality of the Language of MTs Talrbiyaltul Alulald Tebalnalh Students. The targets of this research were school principals, teachers and class VII students at MTs Tarbiyatul Aulad. Data collection techniques include observation, preliminary analysis and documentation. The results of the researchers revealed that this movement of verbal literacy was one of the reasons behind the changes regarding the legal education of students at MTs Talrbiyaltul Alulald. Based on the research that has been carried out, the current translation program at MTs Talrbiyaltul Alulald is effective in increasing the number of natural minerals, this signal has been used to encourage students to return to the school and even outside the school which has active students. always reading books to the amusement of students' bullying.